El espacio público y su importancia en las ciudades: red de intervenciones puntuales para la regeneración del espacio público en la comuna 8 de la ciudad de Neiva (huila), 2021 (2021)
Public spaces are the main source of life in the city, people live and move through it. In them life takes place; Recreation, interactions, permanence among other sensations that can be experienced in public space. In this text, a theoretical, conceptual and practical analysis of different authors and actors with different perspectives will be executed that serve as a fundamental basis for the approach and understanding of issues such as the construction of public space, social relations, the relationship of public space with man and its application in an adverse context where people live for the social and family good.